DEVELOPING THE SCHOOL QUALITY STANDARD AT PRIVATE MADRASAH ALIYAH - Jundatul Afidah; Saadatud Darain; Abdul Malik Karim Amrullah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2022)
Quality issues always have implications for the selling value of an educational institution. This research aims to analyze the quality development strategy in The Private Madrasah Aliyah Manba'ul Hikam Sidoarjo educational institutions. The approach used in this study is a descriptive qualitative approach with data collection techniques in the form of results from observations, interviews, filling out questionnaires, and documentations. Data sources in this study came from school residents such as the headmaster, vice principal, administrator, teachers, and students. The data validity technique uses data triangulation. The data analysis technique used in this research is interactive qualitative by Miles and Huberman, which consists of data reduction, data presentation, and research conclusion. The results obtained in the study explain that the steps for developing quality standards for The Private Madrasah Aliyah Manba'ul Hikam are in the form of (1) developing the governance of teaching and educational staff; (2) development of student governance; and (3) strategies for madrasa heads that are following the quality of the National Education Standards (SNP) which serve as the basis for planning, implementing and supervising education to create quality of education. Independent development of madrasa's quality standards can increase a madrasa's selling value.